2001
DOI: 10.1128/jcm.39.7.2397-2404.2001
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Hantavirus Nucleocapsid Proteins for Serotyping Hantaan, Seoul, and Dobrava Hantavirus Infections

Abstract: Truncated recombinant nucleocapsid proteins (rNPs) of Hantaan virus (HTNV), Seoul virus (SEOV), andDobrava virus (DOBV) were expressed by a baculovirus system. The truncated rNPs, which lacked 49 (rNP50) or 154 (rNP155) N-terminal amino acids of the NPs of HTNV, SEOV, and DOBV, were able to differentiate HTNV-, SEOV-, and DOBV-specific immune sera. Recombinant NP50s retained higher reactivities than rNP155s and were proven useful for enzyme-linked immunosorbent assay (ELISA). The ELISAs based on the rNP50s of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 28 publications
1
73
0
1
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA): Anti-hantavirus IgG in patients was detected by ELISA [2,20,27]. Briefly, 96-well plates were coated with the monoclonal antibody (MAb) E5/G6 [26,47] as a capture antibody and were treated with Block Ace (Dainippon Sumitomo Pharma Co., Ltd., Osaka, Japan) at 37C for 1 hr for blocking.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enzyme-linked immunosorbent assay (ELISA): Anti-hantavirus IgG in patients was detected by ELISA [2,20,27]. Briefly, 96-well plates were coated with the monoclonal antibody (MAb) E5/G6 [26,47] as a capture antibody and were treated with Block Ace (Dainippon Sumitomo Pharma Co., Ltd., Osaka, Japan) at 37C for 1 hr for blocking.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 96-well plates were coated with the monoclonal antibody (MAb) E5/G6 [26,47] as a capture antibody and were treated with Block Ace (Dainippon Sumitomo Pharma Co., Ltd., Osaka, Japan) at 37C for 1 hr for blocking. The Baculovirus-expressed recombinant hantavirus NP of PUUV, DOBV, or HTNV [2,20] was then added to the plates and incubated at room temperature for 1 hr. Sera from clinically diagnosed HFRS patients were diluted to 1:200, added to the plates, and incubated at room temperature for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One is located within the N-terminal 1-120 amino acids and contains linear and cross-reactive epitopes to other hantaviruses (Elgh et al, 1996b;Gott et al, 1997;Jenison et al, 1994;Wang et al, 1993;Yamada et al, 1995). The other is located within the C-terminus and contains conformation-dependent and serotypespecific epitopes (Araki et al, 2001;Morii et al, 1998;Ruo et al, 1991;Yoshimatsu et al, 1996). Previous studies have shown that the N-terminal immunoreactive region is conserved and that those of HTNV, SEOV, and DOBV are cross-reactive, and those of SN and PUUV are cross-reactive .…”
Section: Introductionmentioning
confidence: 99%